“The Balkan Refugee and Migrant Corridor and the Case of North Macedonia” - Ilievski, Zoran. Runcheva Tasev Hristina. (Konrad Adenauer Stiftung, Germany., 2019)
From its inception the European Union has been a preferred destination for refugees fleeing violence and persecution, as well as economic migrants from all over the world. This analysis explores the political consequences of the mixed migration flows moving from the Middle East, through the Balkans on their way to Central and Western Europe in 2015–2016. In addition to the refugees from the Syrian war, displaced persons originating from other parts of the Middle East, Africa, Afghanistan, and elsewhere were joined in Greece by migrants and refugees who were previously settled there, mostly unregistered people, outside the official temporary protection and asylum procedures. This migration phenomenon has encouraged nationalist political forces in the Western Balkan region and in the EU to portray it as a threat to national identity and core values, presenting competing visions about the future of the EU itself. Analyzing the extent to which such nationalistic reactions were evident in the countries along the Balkan mixed migration corridor, a particular focus is placed on the case of the Republic of North Macedonia.
Keywords: migration flows; refugees; Balkan mixed migration corridor; nationalist political forces